Genetic analysis of a black-tailed prairie dog (Cynomys ludovicianus) metapopulation within shortgrass steppe - Roach, Jen L., author; Van Horne, Beatrice, advisor; Antolin, Michael F., advisor; Wilson, Kenneth R. (Kenneth Ray), committee member (Colorado State University. Libraries, 1999)
Black-tailed prairie dogs (Cynomys ludovicianus) in shortgrass steppe currently exist as a metapopulation. Habitat alteration, recreational shooting, agricultural control, and most recently, the introduction of sylvatic plague (Yersinia pestis) have contributed to local colony extinction and a steady decline of C. ludovicianus from its large and continuous historical range. Difficulties in quantifying dispersal have complicated efforts to document the degree of connectedness between isolated colonies. However, patterns of genetic similarity among populations, as measured by neutral molecular markers, provide an estimate of the degree of linkage within a metapopulation. We sampled 13 black-tailed prairie dog colonies in shortgrass steppe in Weld County, Colorado. The history of extinctions and recolonizations of the 13 colonies during the past 18 years is known. We examined 153 prairie dogs for variation at seven microsatelite loci and found moderate levels of genetic differentiation among prairie-dog populations (FST = 0.118). Akaike's Information Criterion was used to model prairie-dog dispersal as a function of genetic distance. Pairwise genetic distances between populations were related to both the distances along drainages (potential dispersal corridors), and to the relative ages of the populations. Cluster analysis revealed that prairie-dog populations are not more closely related to nearest neighbors than to other populations, indicating that populations are not in genetic drift-migration equilibrium and that prairie dogs are likely to disperse among all populations.
Keywords: Black-tailed prairie dog -- Dispersal; Population biology